Gas inflow and AGN-driven outflow in M51. Issue Volume 10:Issue S309(2014) (9th February 2015) - Querejeta, M.; Meidt, S. E.; Schinnerer, E.; García-Burillo, S.; Pety, J.; Hughes, A.; Meier, D.; Bigiel, F.; Kreckel, K.; Blanc, G.
Abstract: We study the feeding and feedback of the nucleus of M51 by considering gravitational torques, responsible for gas inflow, in relation to the local distribution of dense gas.